Management of pedagogical and sports educational institutions in Ukraine - Kubitskyi, Serhii; Saienko, Volodymyr; Demianiuk, Viktor; Mykhasiuk, Kateryna (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The educational system is an essential component and determinant of social development since education functioning quality determines and forms the intellectual potential of society. This article aimed to identify the main trends and promising areas of optimization of the managing process of pedagogical and sports educational institutions. We studied the tendencies of reforming the management process in the educational sphere and the application of modern approaches to the management of pedagogical and sports educational institutions, as well as areas of reforming the academic sphere. This practical, cross-sectional study was carried out through an online survey of 37 managers and teachers of sports and pedagogical educational institutions located in Ukraine. Our study showed that the management process of sports and pedagogical educational institutions can be effective only if it is scientifically substantiated and implemented following the goals of strategic development of educational institutions. The functioning of the management mechanism is based on the understanding of management as a particular function that ensures the feasibility and quality of an educational institution's management. Management approaches are focused on studying the relationships between the components of the management system, external and internal conditions of the institution, and the results of its activities.